2016
DOI: 10.1155/2016/1368103
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Human Papillomavirus Infection and Development of Subsequent Squamous Cell Carcinoma of the Skin

Abstract: The role of cutaneous human papillomavirus (HPV) infection in the development of subsequent cutaneous squamous cell carcinoma (SCC) is unknown. Pathologically confirmed cases of SCC (n = 150) enrolled in a previously conducted case-control study were included in a retrospective cohort study to examine the association of cutaneous HPV at the time of SCC diagnosis with the risk of subsequent SCC development. Data on HPV seropositivity, HPV DNA in eyebrow hairs (EB) and SCC tumors were available from the parent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Genital SCC HPV also plays a role. Indeed, HPV leads to the expression of viral genes E6 and E7, which inactivates tumor suppressor genes [ 32 , 33 ]. High heat shock protein (Hsp)70 levels have been detected in penile SCC.…”
Section: Nmsc and Ak: Factors Involved In The Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Genital SCC HPV also plays a role. Indeed, HPV leads to the expression of viral genes E6 and E7, which inactivates tumor suppressor genes [ 32 , 33 ]. High heat shock protein (Hsp)70 levels have been detected in penile SCC.…”
Section: Nmsc and Ak: Factors Involved In The Pathogenesismentioning
confidence: 99%
“…High heat shock protein (Hsp)70 levels have been detected in penile SCC. This suggests that it may help tumorous cells to survive apoptosis and necrosis, in part because it was also found to be elevated in several other cancers [ 33 ]. In addition, C3 was not detected in penile SCC samples, suggesting that viral proteins are involved in counteracting the host immune response.…”
Section: Nmsc and Ak: Factors Involved In The Pathogenesismentioning
confidence: 99%
“…An association between cSCC and HPV 23 as well as HPV 38 was observed [35]. The study by Hampras et al [36] included 150 patients with cSCC and examined whether the presence of beta HPV types in eyebrow hairs increases the risk of developing another SCC, but there was an inverse association between the two conditions. They noticed that the presence of beta HPV types was associated with a lower risk of developing another SCC, which may be explained by the immunogenic effect of the virus [36].…”
Section: Is There Enough Evidence To Confirm the Etiopathogenic Role mentioning
confidence: 99%
“…The study by Hampras et al [36] included 150 patients with cSCC and examined whether the presence of beta HPV types in eyebrow hairs increases the risk of developing another SCC, but there was an inverse association between the two conditions. They noticed that the presence of beta HPV types was associated with a lower risk of developing another SCC, which may be explained by the immunogenic effect of the virus [36]. Proby et al [33] have shown on transplantation patients that the detection of both beta HPV DNA and antibodies against the same HPV type is associated with an increased risk of developing cSCC [33].…”
Section: Is There Enough Evidence To Confirm the Etiopathogenic Role mentioning
confidence: 99%
“…Within participants of a multinational study focused on the natural history of HPV infection in men (HIM study) [28], DNA from multiple β-HPVs were detected in the male genitals, anal canal and oral samples [29-32]. Furthermore, among these men, any β-HPVs were more prevalent in the genital skin (81.6%) compared to the forearm skin (64.4%) and EBH (60.9%) [33]. Interestingly, β-HPVs were reported to be far less prevalent at the uterine cervix in women (∼15%) [34].…”
Section: Epidemiology Of Beta Hpvmentioning
confidence: 99%